Resposta reprodutiva de ovelhas na IATF submetidas a protocolo de 7 ou 9 dias de permanência do dispositivo de progesterona - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
The objective of this study was to evaluate the reproductive performance of ewes submitted to a protocol of 7 (D7) and 9 (D9) days of permanence of the progesterone device in a protocol for timed artificial insemination by laparoscopy. A total of 220 crossbred ewes (Doper x Santa Inês) were distributed in the treatments according to body weight (52.67 ± 11.76 kg), body condition score (2.5 ± 0.8; scale of 1 –5) and the animal category (multiparous, nulliparous and primiparous). Ewes received an intravaginal device of 0.3 g of progesterone (CIDR®) on day zero, keeping in ewes by for 7 or 9 days, which were the experimental treatments. At the time of P4 withdrawal, ewes received 300 IU of eCG (Folligon®) and 6.70 mg of Dinoprost Tromethamine (Lutalyse®). Insemination was performed between 46 and 59 h after device removal, lasting between 1 and 5 min, without differencing statistical between protocols. The estrus detection rate was higher in the D9 protocol compared to the D7 protocol (82% and 65%, respectively, P = 0.0096). However, D7 tended to increase pregnancy rate on the TAI compared to D9 (45% and 33%, respectively, P = 0.09). The plasma concentration of progesterone at device removal was higher in the D7 protocol than in the D9 protocol (2,35 e 1,22 ng/mL, respectively, P=0,04). We conclude that reducing the length of the estrus synchronization protocol to 7 days is recommended, which improved the reproductive respons e in ewes.
Reproductive response of ftai ewes submitted to a protocol of 7 or 9 days of permanence of the progesterone device
Keywords: Ovelhas - Reprodução; Reprodução animal; CIENCIAS AGRARIAS; Reproductive performance; Estrus synchronization; FTAI by laparoscopy; Desempenho reprodutivo; Sincronização de estro; IATF por laparoscopia; Protocolos